PENENTUAN HARGA POKOK PRODUKSI PADA PT. CENTRAL PROTEINA PRIMA, Tbk - Ramadhan Mulia Lubis; Fachrul Rozi (Worksheet : Jurnal Akuntansi, 2021)
The rapid growth of the business world is reasonable with fierce competition fornew and similar industries. This phenomenon requires companies in manufacturingto compete competitively as experienced by the animal feed industry, especiallyshrimp feed. Marketing of shrimp feed at the end of 2019 increased after decliningsince the first quarter of the third quarter. According to the head of the aquaculturedivision of the Association of Animal Feed Entrepreneurs (GPMT) Haris Muhtadi,the transmission occurred because of an outbreak of disease attacking shrimp andafter the outbreak ended, shrimp production began to compete again. There aremany ways that companies, especially those engaged in shrimp feed, do so. Startingfrom creating low prices to making brand variations with a certain quality measurethat is used as a price differentiator between these products. To get around this, thecompany must have the right strategy and policy, namely by paying attention to thecost of production of its products. The purpose of determining the cost of goodsmanufactured at PT. Central Proteina Prima, Tbk. This is to analyze the differencein cost of goods manufactured between the methods used by the company and thecost of goods manufactured with the full cost and variable cost methods. This studyuses a qualitative descriptive method and the data source is secondary data. Theresults of the study to determine the cost of production is the shrimp feed factory ofPT. Central Proteina Tbk Medan issued a production cost per kilogram of Rp.14.103.5. Meanwhile, the variable cost of the method according to the previoustheory, the value per kilogram is smaller, namely Rp. 14,049, with a difference ofRp. 54.5 per kilogram. If the company sets a price of Rp 19,745 per kilogram usingthe same method, then determining the cost of goods manufactured 0.5% is moreeffective using the theoretical variable cost method. This difference occurs becauseof the grouping of raw material costs and direct labor costs which affect factoryoverhead costs and the cost of goods manufactured.